Exploring the ACE Curriculum as an Innovative Pedagogical Approach - Tesalonika, Asry; Purnama , Grace Kartika; Ismanto, Bambang (SEAMEO SEAMOLEC, 2024)
The government and society have a responsibility to achieve national education goals by providing quality education programs that are tailored to local needs, potential, and situations. Community Learning Centers (CLC) with specific curriculum systems have produced various educational innovations. The Accelerated Christian Education (ACE) Curriculum is one such innovation that has been implemented in various schools around the world to improve the quality of education. This study aims to describe the planning, development, implementation, and evaluation of the ACE curriculum innovation implemented at Destiny Institute Salatiga using a qualitative descriptive approach. Data were collected through interviews with administrators, principals, vice principals of curriculum, and teachers, as well as document studies from the ACE curriculum guidebook. The results of the study showed that the ACE curriculum planning was based on a needs analysis, its development and implementation followed the curriculum structure using the Packet of Accelerated Christian Education (PACE) in learning, and the evaluation was conducted by the school regarding the implementation of the ACE Curriculum. The implementation of the ACE curriculum at Destiny Institute Salatiga has been carried out well in terms of planning, development, implementation, and evaluation.